VALUES OF TOLERANCE IN THE CELEBRATION OF THE PROPHET'S MAULID IN THE VILLAGE TEGALLINGGAH, SUKASADA, BULELENG BALI AND ITS POTENTIAL AS HISTORY LEARNING RESOURCES - Muhari Rahman; Tuty Maryati; I Wayan Pardi (Universitas Pendidikan Ganesha, 2023)
This study aims to find out that: (1) the Celebration of the Prophet Muhammad's Birthday inTegallinggah Village (2) the uniqueness of the Prophet Muhammad's Birthday Celebration inTegallinggah Village (3) The values contained in the Prophet Muhammad's Birthday whichcan be used as a source of learning History. The method used in this research is to use adescriptive qualitative research method. This descriptive qualitative research methodemphasizes a quality of research. There are 3 steps used in this descriptive qualitative research,namely observation, interview and document study. The results of the study show that thebirthday of the Prophet Muhammad was introduced for the first time by the Fatimid dynastylong before Al-Barjanzi was born who is known as the maker of poems praising the ProphetMuhammad. However, the Prophet Muhammad's birthday was really popular during the timeof the governor of Ibril (Iraq), namely Abu Sa'id Al-kukburi during the reign of SultanSalahudin Al-ayyubi. After the leadership of Sultan Salahudin Al-ayyubi, the celebration ofthe Prophet's Birthday eventually spread throughout the world, including Indonesia. Theculture that was brought to Indonesia eventually mixed with the local culture so that theelements at Maulid also contained elements or mixing with local culture. The values that canbe used as a source of historical learning are religious values, social values and cultural values.These three values will later be wrapped in the Historical Social Studies Module.Keywords: History of Mawlid, Culture, Historical Teaching Resources